ERP System Implementation in a Leading LED Manufacturing Firm in Malaysia. A Supply Chain Perspective - Siti Noor Roseamirah Ali; Premkumar Rajagopal; Veera Pandiyan Kaliani Sundram; Shamsul Baharin Saihani; Shereen Noranee (International Journal of Supply Chain Management, 2020)
valuable and quality information exchange to perform their daily operations and long-term action plan. Hence, selecting and embracing the right supply chain or business management software has become essential to organization. Most Malaysian manufacturer in prefer in adopting to an enterprise resources planning (ERP) system. However, implementing ERP system successfully is costly and complex, and often shows high disappointment rates or even abandonment due to need of fit with the business or social culture. The study conducted to explore the ERP system implementation in a manufacturing-based organization from the perspective of supply chain management. The ERP system implementation could have either positive or negative affects towards organization or company in terms of performance and innovation. The empirical data were collected using in-depth interview as an instrument in a LED manufacturing company. The result confirm that data cannot be editing after done click, server down and more procedure and process are the causes of ineffective implementation of ERP system in the company. This study gives insight to all top management and supply chain practitioners in the manufacturing industry company in implementing ERP System. Furthermore, the findings of this study could also be beneficial to all ERP users as they would be able to understand the ERP system implementation in sectors apart from manufacturing industry. Finally, the outcome of this study could be useful to ERP system adopters in different developing countries. This is one of the first studies, which adequately covers the challenges faced on ERP implementation itself in a LED-manufacturing firm.